2019
DOI: 10.1038/s41598-019-56149-9
|View full text |Cite
|
Sign up to set email alerts
|

Jatrorrhizine Balances the Gut Microbiota and Reverses Learning and Memory Deficits in APP/PS1 transgenic mice

Abstract: Alzheimer’s disease (AD) is a complex disorder influenced by both genetic and environmental components and has become a major public health issue throughout the world. Oxidative stress and inflammation play important roles in the evolution of those major pathological symptoms. Jatrorrhizine (JAT), a main component of a traditional Chinese herbal, coptidis rhizome, has been shown to have neuroprotective effects and we previously showed that it is also able to clear oxygen free radicals and reduce inflammatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…Exposure to microbial amyloid may cause misfolding of amyloid in the brain (Cerovic, Forloni & Balducci, 2019). Gv-971, a new anti-AD drug recently launched in China, can remodel the balance of gut microflora, normalize disordered metabolites to reduce Aβ deposition, and ultimately improve cognitive function (Wang et al, 2019a;Wang et al, 2019b). In view of this, probiotics and prebiotics may effectively fight against dementia, which is considered as an important progress in the field of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to microbial amyloid may cause misfolding of amyloid in the brain (Cerovic, Forloni & Balducci, 2019). Gv-971, a new anti-AD drug recently launched in China, can remodel the balance of gut microflora, normalize disordered metabolites to reduce Aβ deposition, and ultimately improve cognitive function (Wang et al, 2019a;Wang et al, 2019b). In view of this, probiotics and prebiotics may effectively fight against dementia, which is considered as an important progress in the field of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, people have conducted extensive research on AD, but its pathogenesis is not clear, and no effective treatment has yet been found. Previous AD studies have focused on brain-related aspects such as the production and degradation of Aβ and abnormal phosphorylation of tau (Wang et al, 2019a;Wang et al, 2019b). In recent years, the gut microbiota has been implicated in the occurrence and progression of AD has become a research hotspot (Vogt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences in either α- or β-diversity have been observed in 5xFAD mice at 9–10 weeks old [ 133 ], although α-diversity is lower in these mice by 6 and 12 months of age [ 134 ]. Nevertheless, α-diversity, that conveys the diversity of species within a single sample, is significantly higher in wildtype mice compared to APP/PS1 mice by 9 months of age [ 135 ], although other studies have reported higher α-diversity in the microbiota of APP/PS1 mice at the same age [ 90 ]. It also seems that α-diversity is diminished with aging in APP/PS1 mice, as an indication of a worse health status of the host with aging [ 132 ].…”
Section: Diet Inflammation and Gut Microbiota In Ad Modelsmentioning
confidence: 99%
“…It also seems that α-diversity is diminished with aging in APP/PS1 mice, as an indication of a worse health status of the host with aging [ 132 ]. On the other hand, β-diversity shows significant differences in the microbiome composition of APP/PS1 mice by 2, 6 [ 90 ] and 9 months of age [ 135 ] when compared with their wildtype counterparts. So, as disease progresses a marked temporal shift in the taxonomic distribution of principal phyla is detected, and the Firmicutes / Bacteroidetes ratio increases in APP/PS1 [ 107 ] and 5xFAD mice [ 131 , 134 ] in an age-dependent manner.…”
Section: Diet Inflammation and Gut Microbiota In Ad Modelsmentioning
confidence: 99%
“…Treatment with jatrorrhizine, a main component of Coptidis rhizome, a traditional Chinese herbal, alleviated learning and memory deficits, reduced the levels of Ab plaques in the cortex and hippocampus of APP/PS1 mice. Jatrorrhizine administration clearly affected mouse microbiota modulating the relative abundance of the most predominant phylum Firmicutes and Bacteroidetes in transgenic mice [175]. Also calorie restriction (CR) was effective in promoting neuroprotective effects and health benefits in different animal models, being also able to counteract AD symptoms [176][177][178].…”
Section: Preclinical Studies In Animal Modelsmentioning
confidence: 99%